Information, Market Incentives, and Student Performance - Braz Camargo; Rafael Camelo; Sergio Firpo; Vladimir Ponczek (Institute for the Study of Labor (IZA), 2014)
This paper uses a discontinuity on the test score disclosure rules of the National Secondary Education Examination in Brazil to test whether test score disclosure affects student performance, the composition of students in schools, and school observable inputs. We find that test score disclosure has a heterogeneous impact on test scores, but only increases average test scores in private schools. Since test score disclosure has no impact on student composition and school observable inputs in both public and private schools, our results suggest that test score disclosure changes the behavior of teachers and school managers in private schools by affecting the market incentives faced by such schools. We also develop a model of school and student behavior to help explain our empirical findings.
Keywords: I20; I21; 330; test score disclosure; market incentives; public and private schools